Sports Training and Physical Fitness of Table Tennis Players at Bali Province Sports Week - Suratmin; I Putu Darmayasa; Wigutomo Gozali; Ni Putu Vivin Indrawati; Hanik Liskustyowati; Daniel Womsiwor (Universitas Pendidikan Ganesha, 2024)
Analysis of the level of success in regional sports development is proven by the number of medals obtained, sometimes without scientific study of the reasons and how to get medals at Porprov, including those held in Bali. Seeing regions that only prioritize medals causes sports coaching to stagnate, be hampered, and reduce players' motivation in regional sports coaching. The aim of the research is to analyze sports coaching and the level of physical fitness of table tennis players in Bali Porprov in 2022. This research uses descriptive methods with a combination of quantitative data and qualitative through surveys. The research sample was 23 table tennis players who took part in Porprov Bali. Data was obtained through observation, coach/player interviews, questionnaires, archives and documentation. The data analysis used is data triangulation. To ensure completeness of data or information, validity and high reliability, qualitative research uses data triangulation techniques. The research results that can be concluded are recommendations for focusing on developing the sport of table tennis in the province of Bali as a superior regional sport targeted at achieving national achievements, and the physical fitness of table tennis players in the 2022 Bali Province Province with the categories very good: 9%, good: 4%, fair: 22%, less: 48%, and very less 17%. The implications of this research are: This research can provide guidance to coaches in designing effective training methods to improve physical performance, endurance, speed and agility in table tennis players.